Piezoelectric effect enhanced flexible UV photodetector based on Ga2O3/ZnO heterojunction. (September 2021) - Wang, H.; Ma, J.; Cong, L.; Zhou, H.; Li, P.; Fei, L.; Li, B.; Xu, H.; Liu, Y.
Abstract: Piezoelectric effect has been used to modulate the transport, separation and recombination of carriers in semiconductors and consequently optimize the performance of various optoelectronic devices such as photodetectors and solar cells. In this paper, a flexible metal-semiconductor-metal (MSM) structure ultraviolet (UV) photodetector (PD) is fabricated by depositing c-axis oriented polycrystalline ZnO layer and amorphous Ga2 O3 (a-Ga2 O3 ) layer on PET substrate. The responsivity to 254 nm light can be increased 3.8 times and the response time decreases 43% by applying a tensile strain of 0.57% on the flexible detector. The improvement of the a-Ga2 O3 /ZnO heterojunction photodetector is explained in terms of the strain-induced modulation of the barrier height and the band offset at the Au/a-Ga2 O3 interface and a-Ga2 O3 /ZnO interface. This work could be great value for the design and fabrication of piezoelectric effect enhanced flexible optoeletronic devices. Graphical abstract: The photodetector performance has been improved by applying a tensile strain to the device. The responsivity to 254 nm and 365 nm light increased 3.8 times (from 0.65 A/W to 2.49 A/W) and 5.2 times (from 0.052 A/W to 0.27 A/W), and the response time decreases 43% (from 258 ms to 147 ms) and 31% (from 624 ms to 433 ms) at 254 nm and 365 nm light by applying a tensile strain of 0.57% on the flexible detector. The enhanced performances can be ascribed to the strain-induced piezopotential at the Au/a-Ga2 O3 (amorphous Ga2 O3 ) interface and a-Ga2 O3 /ZnO interface, which can modulate the barrier height and energy band offset and further regulate the photogenerated carriers separation, transportation and recombination. Image 1 Highlights: Flexible piezoelectric ultraviolet photodetector based on amorphous Ga2 O3 (a-Ga2 O3 )/ZnO heterojunction was prepared. The enhancement of photoresponse performance can be attributed to strain-induced modulation of the barrier height and the band offset at the Au/a-Ga2 O3 interface and a-Ga2 O3 /ZnO interface. The responsivity to 254 and 365 nm light can be increased 3.8 times and 5.2 times, and the response time decreases 43% and 31% by applying a tensile strain of 0.57% on the flexible detector. The flexible detector also maintains excellent stability and reliability after thousand cycles bending.